“Sakon Nakhon Model” Project Drive : A Prototype of Community Innovation to Develop the Grassroots Economy of Sakon Nakhon Province - Noppanatwongsakorn, Rachen; Saenchat, Pissadarn; Phoonkasem, Chainarong; Phetphongphan, Wasin; Kittlertpaisan, Jitti; Vaseenonta, Chanin (Journal of Graduate MCU KhonKaen Campus, 2023)
The purpose of this academic article is to reflect the cooperation of higher education institutions in the area, namely Sakon Nakhon Rajabhat University, Kasetsart University (Chaloem Phrakiat Campus Sakon Nakhon Province), and the Rajamangala University of Technology Isan (Phang Khon Campus), as well as government, political and public sectors that jointly push for the "Sakon Nakhon Model" project. with support from the Science, Technology, Research and Innovation Commission House of Representatives to develop grassroots agriculture by applying science, innovation, and technology to apply to the area according to the Sakon Nakhon model. In the past operations, it has benefited the farmers of Sakon Nakhon Province and can be a role model for the country. At present, the effect has been urgently expanded to other areas to cover the entire province of Sakon Nakhon to promote the local community’s economy to be strong and competitive, so it can be self-reliant and help raise the standard of living and well-being of the people in the community